2004
DOI: 10.1111/j.1469-0691.2004.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro activity of rifabutin against rifampicin-resistant Mycobacterium tuberculosis isolates with known rpoB mutations

Abstract: The relationship between resistance to rifampicin and rifabutin and genetic alterations in the rpoB gene of 41 rifampicin-resistant isolates of Mycobacterium tuberculosis was evaluated. Although 35 isolates with rifampicin MICs > or = 32 mg/L were also rifabutin-resistant, six isolates with rifampicin MICs of 2-16 mg/L were susceptible to rifabutin (MIC < or = 0.5 mg/L). Mutations Asp516Val, Asp516Tyr, Leu533Pro and the double mutation Met515Ile and Leu533Pro influenced susceptibility to rifampicin, but not to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 18 publications
7
47
4
Order By: Relevance
“…The isolate from patient 5 was also phenotypically sensitive to rifampin, notwithstanding the presence of a L452P (codon 533 in E. coli) mutation in the rpoB gene. This mutation has also been associated with both high and low levels of rifampin resistance in the literature (26). A M. tuberculosis strain isolated from this patient in the past had been found to be rifampin resis- tant, suggesting either that this mutation results in a borderline phenotype or, alternatively, that a mixture of rifampin-resistant and -sensitive strains could have been present in this patient, although this was not detected in the sequencing data obtained from either the sputum or culture.…”
Section: Resultsmentioning
confidence: 95%
“…The isolate from patient 5 was also phenotypically sensitive to rifampin, notwithstanding the presence of a L452P (codon 533 in E. coli) mutation in the rpoB gene. This mutation has also been associated with both high and low levels of rifampin resistance in the literature (26). A M. tuberculosis strain isolated from this patient in the past had been found to be rifampin resis- tant, suggesting either that this mutation results in a borderline phenotype or, alternatively, that a mixture of rifampin-resistant and -sensitive strains could have been present in this patient, although this was not detected in the sequencing data obtained from either the sputum or culture.…”
Section: Resultsmentioning
confidence: 95%
“…Among all incident TB cases globally, 3.6% are estimated to have MDR-TB (19), so a series of new drugs or alternatives for treatment of MDR-TB has been recommended by WHO since 2008 (20). Rifabutin (Rfb) has been one of the most efficacious drugs and the first-line oral agent recommended by WHO for MDR-TB, but Rfb sometimes has cross-resistance to rifampin (RIF) (2,4,15), which implies that the characterization of rpoB mutations in Rfb-resistant (Rfb r ) isolates is not completely the same as that of rpoB mutations in RIF-resistant (RIF r ) isolates. There have been few data supporting this conjecture to this day because of a lack of characterization of rpoB mutations in Rfb r clinical Mycobacterium tuberculosis isolates, so it is very hard to identify the Rfb r isolates from RIF r isolates, even though so many molecular assays for prediction of rifampin susceptibility have been established (8,1,13,3,5).…”
mentioning
confidence: 99%
“…8,33,34 However, some studies have also reported other uncommon mutations inside and outside of the "hot-spot" region that were regularly or even systematically missed by standard, World Health Organization-endorsed DST methods. 35,36 The most sensitive limit of detection theoretically possible is three copies per PCR reaction, assuming a Poisson distribution. 37 The analytical sensitivity is defined as the concentration that can be detected with reasonable certainty (95% probability is commonly used) with a given analytical procedure.…”
Section: Discussionmentioning
confidence: 99%